Chicken : Soups, Salads, Stir-Fries, Curries, Grills, Roasts - Directed by Clark, Pamela (Australia ACP, 2006)
Divided into two chapters - weeknights and weekends. The recipes in weeknights are fast such as salads, grills, stir-fries, barbecues, whereas the weekend chapter contains slower-cooked dishes such as roasts, casseroles, curries and soups.